Investigation of ergonomic risk factors among male workers in a medical manufacturing company in northern Malaysia - Athirah, Yusof; Nurul Shahida, Mohd Shalahim (Malaysian Public Health Physicians’ Association, 2020)
The medical manufacturing industry is currently one of the sectors with great potential growth in Malaysia, which offers numerous job opportunities to local and foreign workers. The growing proportion of workers in this industry means that a large number of workers are potentially exposed to ergonomic risk factors at the workplace, which may consequently affect their health. Thus, this study was carried out is to investigate the ergonomic risk factors and the prevalence of musculoskeletal disorders among male workers in a medical manufacturing company in northern Malaysia. Eight industrial workers (n = 8) were recruited from two Plastic Technology (PT) departments to participate in this study. Observations were made by recording the participants performing two tasks (manual lifting of containers and bags of chemicals) using a video camera at the PT1 and PT3 departments. The participants’ personal information and their job-related characteristics were first collected using a demographic questionnaire. Next, the Cornell Musculoskeletal and Hand Discomfort Questionnaire (CMDQ) was used to evaluate the prevalence of musculoskeletal disorders among workers while Manual Handling Assessment Charts (MAC) were used to assess the most common risk factors during the lifting operations. The results showed that the highest prevalence of musculoskeletal disorders among the male workers at the medical manufacturing company was at the lower back (83.17%), upper back (4.38%), right shoulder (3.49%), and left shoulder (3.49%). Based on the results of the MAC, 100% of the participants were at high risk of injury from postures in the vertical lift zones, torso twisting, and sideways bending. In addition, 87.5 and 62.5% of the participants were at high risk of injury based on their hand distance from the lower back and grip on the load, respectively. The results of this study can serve as a guideline to implement interventional ergonomics programmes at the workplace and improve the musculoskeletal health of workers in the medical manufacturing industry in Malaysia.